Review of wrongful convictions following police misconduct: A study of the English Criminal Cases Review Commission - Hoyle, C (Walter de Gruyter GmbH, 2023)

(untitled)
The Criminal Cases Review Commission (CCRC) reviews possible wrongful convictions in England, Wales, and Northern Ireland, referring back to the Court of Appeal cases where there is a ›real possibility‹ that the conviction is unsafe. This article presents findings from a four-year empirical study of decision-making within the CCRC. It explores how Commission staff exercise discretionary powers in identifying and investigating possible wrongful convictions, referring just a few back to the Court. Since its inception in April 1997, the CCRC has received almost 29,000 applications and referred 797 back to the Court of Appeal. Of these referrals, the Court has quashed the conviction in 542 cases. In 2019-20, the CCRC received 1,334 applications, and in 2020-21, 1,142. It focuses on a sample of cases that turned on police misconduct in pursuit of a socio-legal contribution to our understanding of the response of the state to claims of wrongful conviction. It demonstrates that caseworkers’ approaches to investigation and decision-making is shaped by the law and internal policies such that reasonably consistent decision frames emerge.